Theoretical substantiation of the petroleum hydrocarbons destruction by specific microflora using anaerobic digestate - Ablieieva, Iryna (Видавництво Львівської політехніки, 2020)
Implementation of the proposed approach to bioremediation of oil-contaminated soils provides an intensification of the hydrocarbons degradation process biologically using a digestate as a bio-stimulant, contributes to the production of an ecologically safe substrate, and excludes its toxicity to living organisms due to the degradation of petroleum hydrocarbons.
Keywords: iodegradation; biodestructors; digestate; oildestructive bacteria; oil contaminated soil